THE EFFECTS OF Trichoderma harzianum ON SMOTH AND YIELD OF CALABASH CULTIVETED ON PEAT SOIL - LIANTI LIANTI; DWI ZULFITA; SURACHMAN SURACHMAN (Jurnal Sains Pertanian Equator, 2016)
ABSTRACT This research aimed to obtain the best application dosage of Trichoderma harzianum on growth and yield of calabash cultivated on peat soil. The study was carried out in experimental field of Tanjungpura University started from 2nd May  until 25th July 2016. The crops were planted in polybag according to completely randomized design with 6 levels of treatment is : t0 = without cocentrations of Trichoderma harzianum, t1 = 10 ml/polybag cocentrations of Trichoderma harzianum , t2 = 20 ml/polybag cocentrations of Trichoderma harzianum, t3 = 30 ml/polybag cocentrations of Trichoderma harzianum, t4 = 40 ml/polybag  cocentrations of Trichoderma harzianum, dan t5 = 50 ml/polybag cocentrations of Trichoderma harzianum.  The variables observed in this research included root volume, leaf chlorophyll, leaf area, dry biomass, fruit biomass, fruit diameter, fruit length, and number of fruits in a crop plant. The results showed that the Trichoderma harzianum significant affect chlorophyll leaf, total leaf area, dry biomass of plant, fruits biomass,and diameter for root volume, fruit length and number of fruits in a crop plant not significant. The results not get the best but get effective concentrations is 20 ml/polybag of Trichoderma harzianum for yield fruit biomass of gourds on peat soil.   Keyword : calabash, peat soil, Trichoderma harzianum.